Branch vessel occlusion in aneurysm treatment with flow diverter stent - Hohenstatt, Sophia; Arrichiello, Antonio; Conte, Giorgio; Craparo, Giuseppe; Caranci, Ferdinando; Angileri, Alessio; Levi, Daniel; Carrafiello, Gianpaolo; Paolucci, Aldo (Acta Biomedica Atenei Parmensis, 2020)
Flow diverter placement for treatment of intracranial aneurysms gained growing consensus in the past years. A major concern among professionals is the side branch coverage which leads in some cases to vessel occlusion. However, the lost vessel patency only infrequently is accompanied by a new onset of neurological deficits secondary to ischaemic lesions. A retrospective analysis of all patients treated with flow diversion at our hospital was aimed to better understand this phenomenon in order to formulate a hypothesis about the causes. We concluded that vessel occlusion occurs due to a reduced blood pressure gradient in those vessels with a strong collateral or anastomotic vascularization that refurnishes the same distal vascular territories. Indeed, we detected no new brain infarction since blood flow was always guaranteed.